Kemampuan Menganalisis Makna Tersirat Struktur Teks Hikayat “Si Miskin” Siswa Kelas X SMA Muhammadiyah 1 UNISMUH Makassar - Jusnina Jusnina; Rosmini Madeami; Abdul Wahid (Universitas Katolik Widya Karya Malang, 2023)
The aim of this study is to find out the ability to analyze the implied meaning of the text structure of the saga